2022
DOI: 10.1055/s-0041-1741030
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Androgen Predictive Effects on Clinical and Metabolic Abnormalities of Polycystic Ovary Syndrome

Abstract: Objective To examine the possible effects of adrenal prohormones in the prediction of clinical and metabolic abnormalities in women with polycystic ovary syndrome (PCOS). Methods The present study enrolled 299 normal cycling non-PCOS, 156 normoandrogenemic, and 474 hyperandrogenemic women with PCOS. Baseline characteristics were compared using a chi-squared test or analysis of variance (ANOVA) as appropriate. The roles of adrenal prohormones and their ratios with total testosterone in predicting co-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Notably, when DHEAS levels were ≥ 7.69umol/ml, there was a significant negative impact on the CPR and CLBR. Similarly, a separate study indicated that DHEA and DHEAS could serve as better predictors of abnormal anthropometric and biochemical parameters in women with PCOS, which may be associated with fertility issues [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when DHEAS levels were ≥ 7.69umol/ml, there was a significant negative impact on the CPR and CLBR. Similarly, a separate study indicated that DHEA and DHEAS could serve as better predictors of abnormal anthropometric and biochemical parameters in women with PCOS, which may be associated with fertility issues [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…(6,18,22) Chronic exposure to androgens directs macrophages to adipocytes, which induce their hypertrophy, leading to visceral fat accumulation, causing obesity. (18,23) Obesity is present in 56% of patients with PCOS (10) and its presence can aggravate metabolic and reproductive disorders associated with it. (9) Studies have shown that patients with PCOS are 4 times more likely to have MS. (8,24) Thus, PCOS brings complex health consequences, in which it affects the quality of life of women in the short and long term.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Women with PCOS are more likely to accumulate fat, especially abdominal fat. (18,23) Free fatty acids activate Toll-like receptors (TLRs), especially TLR4, which plays an inhibitory role in the IR β-subunit pathways by increasing the phosphorylation of JNK at serine, making a vicious cycle of IR. (26,34) 2.3 Fetal Metabolic Programming and SOP Due to the multifactorial causes of PCOS, (7,11) some studies suggest that during fetal development changes occur that increase the chance that offspring will present PCOS as adolescents, (1) a process known as metabolic programming.…”
Section: Glucose Homeostasis and Sopmentioning
confidence: 99%